2022
DOI: 10.1002/chem.202201660
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent Interactions Involving Group 6 in Biological Systems: The Case of Molybdopterin and Tungstopterin Cofactors

Abstract: In this study we propose to coin the term Wolfium bond (WfB) to refer to a net attractive force (noncovalent interaction) between any element of group 6 and electron donor atoms (neutral molecules or anions) and to differentiate it from a coordination bond (metal‐ligand interaction). We provide evidence of the existence of this interaction by inspecting the X‐ray crystal structure of proteins containing Molybdopterin and Tungstopterin cofactors from the Protein Data Bank (PDB). The plausible biological role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…18−20 A "σ-hole interaction" typically implies an electrophilic region from the σ-hole donor molecule (usually characterized by a positive electrostatic potential) located along the vector of a covalent bond (e.g., a C−Br bond in CBrF 3 or an Sb−F bond in SbF 3 ) that favorably interacts with a Lewis base (e.g., a lone pair, a π-system, or an anion). 21 Recently, the "σ-hole" concept has been expanded to the transition-metal elements (d-block of the periodic table) through the discovery of several metal-based NCIs, such as Wolfium (group 6), 22 Matere (group 7), 23 Osme (group 8), 24 Regium (group 11) 25,26 and Spodium (group 12) bonds. 27,28 In biology, metal complexes have been considered as a very powerful class of biological agents for decades.…”
Section: ■ Introductionmentioning
confidence: 99%
“…18−20 A "σ-hole interaction" typically implies an electrophilic region from the σ-hole donor molecule (usually characterized by a positive electrostatic potential) located along the vector of a covalent bond (e.g., a C−Br bond in CBrF 3 or an Sb−F bond in SbF 3 ) that favorably interacts with a Lewis base (e.g., a lone pair, a π-system, or an anion). 21 Recently, the "σ-hole" concept has been expanded to the transition-metal elements (d-block of the periodic table) through the discovery of several metal-based NCIs, such as Wolfium (group 6), 22 Matere (group 7), 23 Osme (group 8), 24 Regium (group 11) 25,26 and Spodium (group 12) bonds. 27,28 In biology, metal complexes have been considered as a very powerful class of biological agents for decades.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The study and utilization of noncovalent interactions involving metal centers are attracting the attention of the scientific community. In particular, theoreticians and crystallographers are putting effort into understanding the physical nature of such contacts [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Starting from the pioneering works of Brinck et al on regium bonds (group-11) [ 1 , 2 ], the field has been extended toward group 12 (spodium bonds) [ 3 , 4 ], group 6 (wolfium bonds) [ 5 ], group 7 (matere bonds) [ 6 ] and group 8 (osme bonds) [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, theoreticians and crystallographers are putting effort into understanding the physical nature of such contacts [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Starting from the pioneering works of Brinck et al on regium bonds (group-11) [ 1 , 2 ], the field has been extended toward group 12 (spodium bonds) [ 3 , 4 ], group 6 (wolfium bonds) [ 5 ], group 7 (matere bonds) [ 6 ] and group 8 (osme bonds) [ 7 , 8 , 9 ]. Apart from the relevance of these interactions in the solid state and in biological systems [ 10 ], it has been demonstrated that regium bonds are also important in catalysis [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the strongest σ-holes are thus predictable when a heavy-metal atom is covalently bonded to a more electron-withdrawing group. The attractive pull/hold between the elements of group 14 (Lewis acids) , and electron-rich atoms (Lewis bases) is described as a tetrel bond (TtB). The tetrel bonding interactions can be observed with an experimental 13 C NMR spectral study. , In recent years, scientists have tried to develop the σ-hole bond concept from main-group to transition-metal elements, where elements of group 6 (wolfium bond), group 7 (matere bond), group 8 (osme bond), group 11 (regium/coinage bond) , and group 12 (spodium bond) , are the latest members to join the σ-hole family. As lead is the heaviest metal of group 14 elements, it is more likely to form strong σ-holes compared to other members of the group.…”
Section: Introductionmentioning
confidence: 99%